Ethical Challenges that Arise at the Community Interface of Health Research: Village Reporters' Experiences in Western Kenya. Issue 1 (22nd March 2013) - Chantler, Tracey; Otewa, Faith; Onyango, Peter; Okoth, Ben; Odhiambo, Frank; Parker, Michael; Geissler, Paul Wenzel
Abstract Community Engagement (CE) has been presented by bio‐ethicists and scientists as a straightforward and unequivocal good which can minimize the risks of exploitation and ensure a fair distribution of research benefits in developing countries. By means of ethnographic fieldwork undertaken in Kenya between 2007 and 2009 we explored how CE is understood and enacted in paediatric vaccine trials conducted by the Kenyan Medical Research Institute and the US Centers for Disease Control (KEMRI/CDC). In this paper we focus on the role of paid volunteers who act as an interface between villagers KEMRI/CDC. Village Reporters' (VRs) position of being both with the community and with KEMRI/CDC is advantageous for the conduct of trials. However it is also problematic in terms of exercising trust, balancing allegiances and representing community views. VRs role is shaped by ambiguities related to their employment status and their dual accountability to researchers and their villages. VRs are understandably careful to stress their commitment to self‐less community service since it augments their respectability at community level and opens up opportunities for financial gain and self‐development. Simultaneously VRs association with KEMRI/CDC and proximity to trial participants requires them to negotiate implicit and explicit expectations for material and medical assistance in a cultural setting in which much importance is placed on sharing and mutuality. To ensure continuity of productive interactions between VRs, and similar community intermediaries, and researchers, open discussion is needed about the problematic aspects of relational ethics, issues concerning undue influence, power relations and negotiating expectations.